Kahramanmaraş ansiklopedisi (Kahramanmaraş Kahramanmaraş Kahramanmaraş Kahramanmaraş Kahramanmaraş Kahramanmaraş)
5 cilt (1. c. ix, 446 sayfa ; 2. c. x, 565 sayfa ; 3. c. viii, 602 sayfa ; 4. c. viii, 508 sayfa ; 5. c. viii, 497 sayfa ; 6. c. viii, 424 sayfa ; 7. c. viii, 502 sayfa)